2016
DOI: 10.15226/jnhfs.2016.00163
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and undernutrition in treated HIV patients a (post-) conflict setting: A cross sectional study from Goma, Eastern Democratic Republic of Congo

Abstract: Objective: To assess the prevalence of food insecurity and its impact on nutritional status among HIV infected patients on antiretroviral therapy in a conflict and post conflict setting.Design: Cross-sectional study.Setting: This Goma multicenter cross-sectional study was carried out from February 1 st to March 3 rd , 2016.Subjects: Data on nutritional status among 583 HIV-infected patients on ART were measured using Body Mass Index as a proxy. Food insecurity was the primary independent variable and was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
4
8
0
2
Order By: Relevance
“…The nding of the study showed household food insecurity was signi cantly associated with under nutrition. This nding was consistent with study conducted in Humera hospital, West shewa zone ( ve times) and Goma (14). Similarly, nearly the same report from Study conducted in Bale Goba (22) and study conducted in Asella Town (44).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The nding of the study showed household food insecurity was signi cantly associated with under nutrition. This nding was consistent with study conducted in Humera hospital, West shewa zone ( ve times) and Goma (14). Similarly, nearly the same report from Study conducted in Bale Goba (22) and study conducted in Asella Town (44).…”
Section: Discussionsupporting
confidence: 90%
“…HIV-infected persons are at higher risk for undernutrition, and certain conditions can magnify the risk, such as anorexia, di culty swallowing or painful swallowing, malabsorption and diarrhea, altered metabolism of nutrients, increased utilization of nutrients, and greater loss of nutrients (4). Not only this but also, there are many factors associated with HIV/AIDS undernutrition among them household food insecurity, lack of nutritional counseling, educational status, and economic status are evidenced by many studies (6,10,14,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vulnerabilidade da população que convive com o vírus HIV à Insegurança Alimentar é alta, devido ao próprio curso da patologia que se apresenta com achados clínicos como: náuseas crônicas, alteração do paladar, perda de apetite, dificuldades em mastigar e/ou deglutir, diarréias...que levam à redução da ingestão e/ou má absorção concorrendo para deficiência de micronutritentes (Akilimali et al, 2016). Em relação a isso, no estágio precoce da doença é observado o comprometimento do status nutricional de vitaminas, como complexo B em especial a vitamina B12, ácido fólico e minerais como zinco, selênio dentre outros (Pavarina, 2008;Matthew, 2004;Batista, et al, 2021).…”
Section: Introductionunclassified
“…Estudos observacionais também confirmam que indivíduos portadores do vírus HIVaids apresentam uma rotina alimentar inadequada, caracterizada pela alta ingestão de açúcar, gordura saturada e sódio, além da ingestão insuficiente de fibras, frutas, vegetais e cereais integrais (Tanaka et al,2015). A baixa quantidade e qualidade dos alimentos compromete o estado nutricional com deficiência de macro e micronutrientes precipitando, inclusive, a ocorrência de infecções oportunistas, prejudicando a adesão ao tratamento antirretroviral (TARV), agravando a imunodepressão e criando um círculo vicioso (Akilimali et al, 2016;Soares, 2015).…”
Section: Introductionunclassified